2022
DOI: 10.3389/fgene.2022.879108
|View full text |Cite
|
Sign up to set email alerts
|

Trans-Renal Cell-Free Tumor DNA for Urine-Based Liquid Biopsy of Cancer

Abstract: Cancer biomarkers are a promising tool for cancer detection, personalization of therapy, and monitoring of treatment response or recurrence. “Liquid biopsy” commonly refers to minimally invasive or non-invasive sampling of a bodily fluid (i.e., blood, urine, saliva) for detection of cancer biomarkers such as circulating tumor cells or cell-free tumor DNA (ctDNA). These methods offer a means to collect frequent tumor assessments without needing surgical biopsies. Despite much progress with blood-based liquid bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…6 Despite the lack of understanding about how DNA crosses the renal barrier, several studies have shown the presence of transrenal cfDNA in urine for different physiological and pathological conditions, such as pregnancy, cancer and inflammation. 5,6,8,10,11 Recent studies showed that cell-free nucleic acids and tumor DNA are shed into the circulation and pass the renal barrier to be excreted in urine. 12,13…”
Section: Transrenal Vs Nontransrenal Urinary Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Despite the lack of understanding about how DNA crosses the renal barrier, several studies have shown the presence of transrenal cfDNA in urine for different physiological and pathological conditions, such as pregnancy, cancer and inflammation. 5,6,8,10,11 Recent studies showed that cell-free nucleic acids and tumor DNA are shed into the circulation and pass the renal barrier to be excreted in urine. 12,13…”
Section: Transrenal Vs Nontransrenal Urinary Biomarkersmentioning
confidence: 99%
“…5,6 The large size class, cellular DNA, originates from genital tract cells or cell debris shed into urine, while the small size class, cell-free DNA (cfDNA), mainly originates from glomerular filtration of blood cfDNA. [5][6][7][8] Cell-free and circulating nucleic acids in blood are the results of apoptosis and/or necrosis in actively proliferating healthy cells or tumor tissue. Apoptosis can be distinguished from necrosis based on the produced DNA fragment size.…”
Section: Transrenal Vs Nontransrenal Urinary Biomarkersmentioning
confidence: 99%
“…The concentration of cell-free DNA in liquid biopsies, in particular such as urine, is usually low and varies considerably among different specimens and type of disease. 21 Taking into consideration the challenge of low-abundance cfDNA targets in liquid biopsies, 2,7 a major advantage of urine as a biological specimen for molecular diagnostics resides in the possibility of volume up-scaling, thereby increasing detection sensitivity. [23][24][25][26] The current investigation was devoted to the question if open-end increment of specimen F I G U R E 5 Urine cfDNA concentrations of 32 individuals (EGFR gene exon 21,119 bp) ranged from 121 to 19,049 copies/mL (median 1642, IQR 605-5388).…”
Section: Discussionmentioning
confidence: 99%
“…Circulating tumor DNA, sometimes referred to as cell-free DNA, consists of nucleic acid fragments released by malignant cells via both passive (e.g., necrosis) and active (e.g., exocytosis) processes 19 . In the past several years, several institutions have developed robust experimental protocols to readily isolate ctDNA derived from HPV + OPSCC tumors in patients' plasma and urine 13,20–23 . Such protocols utilize quantitative polymerase chain reaction, digital droplet polymerase chain reaction, or capture-based next-generation sequencing to detect minute quantities of the highly conserved and oncogenic HPV E6 and/or E7 oncogenes 24 .…”
Section: Current State Of Liquid Biopsies In Hpv+ Opsccmentioning
confidence: 99%
“…19 In the past several years, several institutions have developed robust experimental protocols to readily isolate ctDNA derived from HPV + OPSCC tumors in patients' plasma and urine. 13,[20][21][22][23] Such protocols utilize quantitative polymerase chain reaction, digital droplet polymerase chain reaction, or capture-based next-generation sequencing to detect minute quantities of the highly conserved and oncogenic HPV E6 and/or E7 oncogenes. 24 The purported advantages of ctDNA biomarkers in managing HPV + OPSCC include avoiding painful oropharyngeal biopsies, reducing operating room costs and utilization, using them as prognostic and predictive biomarkers, and improving the precision of diagnosis relative to computed tomography, magnetic resonance imaging, and position emission tomography for surveillance.…”
Section: Current State Of Liquid Biopsies In Hpv + Opsccmentioning
confidence: 99%